Cyclic Loading on Composite Repair of Corroded Steel Pipelines - P, Nitheesh Kumar; K, Vishwas Chandra; Balaganesan, G; K, Jayakumar; Mahajan, Puneet (Defence Science Journal, 2024)
The study aims to determine how cyclic loading affects the structural integrity and lifespan of composite repair systems used to restore corroded steel pipelines. As specified in Annexure C of the ISO 24817 repair code, pipe specimens are machined to produce flaws with 80% wall loss. Testing under static and cyclic pressure loading is done as per ASTM D2992 and ASTM D2143. Static pressure loading is accomplished by continually pressurizing the pipe specimen, and burst pressure is assessed. Various Rc-ratios or levels of cyclic loading severity are used in cyclic pressure loading tests. Each case's number of cycles before failure is determined experimentally, and the service de-rating factor is assessed in accordance with ISO 24817. The 235 bar pressure was sustained by the static-loaded repaired pipe specimens with 80% wall loss, and the failure was catastrophic. At around 7000 cycles, the cyclically loaded repaired samples with 80% wall loss failed, and the failure manifests as debonding or a leak.